Creolizing the nation - Sealey, Kris, 1978- (Book collections on Project MUSE., 2020)
"Creolizing the Nation develops a new account of how to understand difference, locally and globally. The book analyzes what it means concretely to create emancipatory communities of composite cultures and ways of being"--